Frontispiece: Short Total Synthesis of (±)‐γ‐Lycorane by a Sequential Intramolecular Acylal Cyclisation (IAC) and Intramolecular Heck Addition Reaction. Issue 20 (6th April 2017) - Monaco, Alessandra; Szulc, Blanka R.; Rao, Zenobia X.; Barniol‐Xicota, Marta; Sehailia, Moussa; Borges, Bruno M. A.; Hilton, Stephen T.
Abstract : The pentacyclic structure of the natural product (±)‐γ‐lycorane was synthesized by a new sequential Lewis acid mediated intramolecular acylal cyclisation (IAC)/Heck coupling approach. A range of bicyclic heterocycles was also synthesized by using this methodology in good yields demonstrating the potential of the IAC reaction to access complex heterocycles. For more details, see the Communication by S. Hilton et al. onpage 4750 ff.